Prediction of Water Discharge and Sediment in Teak Forested Areausing Artificial Neural Network Model - Nining Wahyuningrum (Jurnal Penelitian Kehutanan Wallacea, 2017)
Information on the relationship of rainfall with discharge and sediment are required in watershed management.This relationship is known to be highly nonlinear and complex. Although discharge and sediment has been monitored continuously, but sometimes the information is not or less complete. In this condition, modeling is indispensable. The research objective is to create a model to predict the monthly direct runoff and sediment using Artificial Neural Network (ANN).The model was tested using rainfall data at t-3 and t-4 as input, and discharge and sediment at t+3 and t+4 as output. The data used is the data from 2001 to 2014. The results showed that of some models tested there are two models for the prediction of discharge and two models for sediment.The model was chosen because it has the smallest MSE, the largest R2and satisfying K (0.5 to 0.65).Thus,these models can be used to predict discharge andsediment for a period of t+3 and t+4.Prediction of discharge of t+3 and t+4 may use Q t+3= 0,64 Q t-3+ 0,05 and Q t+4= 0,65 Q t-4+ 0,074 res pectively, while for predicting sediment of t+3 and t+4 may use equations QS t+3= 0,45 QS t-3+ 0,052 and QS t+4= 0,45 QS t-4+ 0,052. This ANN modeling can be applied to predict the flow and sediment in other locations with an architecture adapted to the conditions of available data.